Technology and digital transformation for the structural reform of the sports industry: Building the roadmap - Magaz-González, A. M.; García-Tascón, M.; Sahelices-Pinto, C.; Gallardo, A. M.; Guevara Pérez, J. C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The COVID-19 pandemic in 2020, has accelerated technological immersion into society, economy and public administrations. The sports organisations are no strangers to this digitisation and must carry out their own digital transformation. However, investment in digital technology must be preceded by a diagnosis of the technological needs of each sports entity. Said mapping will help organisations know the most appropriate technological tools for their core businesses so they can properly design their digital transformation strategies. The objectives of this study were to design and create a tool to understand the digital structure of Spanish sports. The result has been the configuration of an instrument that includes the description of different technologies and different digital competencies specific to the sports industry, and which allows individuals to know the use, importance, perceived difficulty of use and economic accessibility of available technologies, as well as the degree of developed competency in the different sports organisations. It is concluded that the creation and application of a consultation instrument on digitalisation is the first and necessary step to carry out relevant, in-depth, valid and replicable research, which allows information to be gathered on the digitalisation needs of sports organisations to design their digital transformation roadmap and that the aids for digital transformation is distributed efficiently.